Live Intravital Imaging of Cellular Trafficking in the Cardiac Microvasculature—Beating the Odds - Kavanagh, Dean Philip John; Kalia, Neena (Frontiers in Immunology, 2019)
Although mortality rates from cardiovascular disease in the developed world are falling, the prevalence of cardiovascular disease (CVD) is not. Each year, the number of people either being diagnosed as suffering with CVD or undergoing a surgical procedure related to it, such as percutaneous coronary intervention, continues to increase. In order to ensure that we can effectively manage these diseases in the future, it is critical that we fully understand their basic physiology and their underlying causative factors. Over recent years, the important role of the cardiac microcirculation in both acute and chronic disorders of the heart has become clear. The recruitment of inflammatory cells into the cardiac microcirculation and their subsequent activation may contribute significantly to tissue damage, adverse remodelling, and poor outcomes during recovery. However, our basic understanding of the cardiac microcirculation is hampered by an historic inability to image the microvessels of the beating heart – something we have been able to achieve in other organs for over 100 years. This stems from a couple of clear and obvious difficulties related to imaging the heart – firstly, it has significant inherent contractile motion and is affected considerably by the movement of lungs. Secondly, it is located in an anatomically challenging position for microscopy. However, recent microscopic and technological developments have allowed us to overcome some of these challenges and to begin to answer some of the basic outstanding questions in cardiac microvascular physiology, particularly in relation to inflammatory cell recruitment. In this review, we will discuss some of the historic work that took place in the latter part of last century towards cardiac intravital, before moving onto the advanced work that has been performed since. This work, which has utilised technology such as spinning-disk confocal and multiphoton microscopy, has - along with some significant advancements in algorithms and software - unlocked our ability to image the ‘business end’ of the cardiac vascular tree. This review will provide an overview of these techniques, as well as some practical pointers towards software and other tools that may be useful for other researchers who are considering utilising this technique themselves.